Determinants of Fluid Restriction Adherence among Hemodialysis Patients: A Single-Center Cross-Sectional Study - Yulianti, Yeni; Tresnawan, Teten (Media Publikasi Cendekia Indonesia, 2025)
Fluid restriction compliance refers to a patient's adherence to the prescribed limit of fluid intake to maintain optimal health. This compliance is influenced by factors such as age, education level, family support, and knowledge. The purpose of this study was to explore how these factors impact fluid restriction adherence among hemodialysis patients. This correlational research used a cross-sectional design with a sample of 155 hemodialysis patients from Jampangkulon Regional Hospital, selected through proportional random sampling. Data were collected via a questionnaire and analyzed using chi-square and logistic regression. The study found that a majority of patients were compliant with fluid restrictions (71.0%), and most possessed good knowledge on the topic (80.6%). Bivariate analysis identified significant effects of age (p=0.030), education (p=0.041), family support (p=0.015), and knowledge (p=0.001) on compliance. After controlling for all factors in a logistic regression model, knowledge emerged as the sole statistically significant predictor of compliance (p=0.028). In conclusion, while age, education, family support, and knowledge were all correlated with adherence, knowledge was the most significant factor in predicting compliance. It is recommended that Jampangkulon Regional Hospital enhance educational programs and involve families in patient care to improve compliance.